Surveying social adversity in pregnancy: The antenatal risk burden experienced by Australian women. (14th February 2018) - Goldfeld, Sharon; D'Abaco, Elise; Bryson, Hannah; Mensah, Fiona; Price, Anna MH
Abstract : Aim: Many, varied, antenatal risk factors can adversely impact children's health, behaviour and cognition. Understanding the antenatal risk factors experienced by women can help identify which families are most likely to benefit from additional early supports; however, there is a dearth of published Australian antenatal risk data. This study aimed to determine the prevalence and co‐occurrence of a broad range of risk factors in a community‐based sample of pregnant Australian women. Methods: A brief risk factor survey (10 items, including age, social support, health, smoking, stress or anxious mood, education, household income, employment) completed by pregnant women attending the antenatal clinic waiting rooms of 10 public maternity hospitals, which were selected for their provision of care to areas with fewer socio‐economic resources in the states of Victoria and Tasmania, between May 2013 and August 2014. Results: A total of 5586 women participated, with an average age of 29.0 years and gestation of 26.9 weeks. The most prevalent antenatal risk factors were poorer global health (38.9%), not finishing high school (33.5%) and smoking (14.9%), all proportions higher than the general population. Most women reported at least one risk factor (68.6%), with 21.5% reporting ≥3. There was a high degree of co‐occurrence between risk factors, especially the three most prevalent. Conclusions: This study reveals the considerable and varied risk burden experienced by Australian women during pregnancy. By understanding where need is greatest and tailoring support accordingly, risk factor assessment provides an opportunity to address equity through health care, ultimately optimising the future developmental outcomes of all children.